The Division of Markets is Limited by the Extent of Liquidity (Spatial Competition With Externalities) - Economides, Nicholas (American Economic Review, 1988)
Liquidity considerations will limit the number of markets in a competitive economy. Welfare implications are ambigious. Since liquidity is a positive externality, there may be too little liquidity per market at a noncooperative equilibrium and too many markets compared to the surplus-maximizing market structure. But liquidity is also self-reinforcing. Given an existing equilibrium, new markets may not open because nobody wants to use a new market with low liquidity. There may be too few markets to achieve efficiency. A nondiscriminating monopolist will operate smaller and more numerous markets compared to optimality as well as to the equilibrium of independent auctioneers. Copyright 1988 by American Economic Association.